CODE-MIXING FUNCTIONS IN CONVEYING CONVERSATIONAL IMPLICATURE IN AZKA-DEDDY YOUTUBE PODCASTS - Evril Stefie Goranni Manik; Slamet Setiawan; Lina Purwaning Hartanti; Ayunita Leliana (Universitas Negeri Surabaya, 2026)
In bilingual digital communication, code-mixing is used not only to combine two languages but also to help speakers convey meaning indirectly. This study aims to analyze the functions of code-mixing that convey conversational implicature in Azka Corbuzier's utterances when speaking with Deddy Corbuzier on a YouTube podcast. This study identifies the types of code-mixing, the types of conversational implicature, and the functions of code-mixing in conveying conversational implicature in Azka Corbuzier's code-mixed utterances during his YouTube podcast conversations with Deddy Corbuzier. This study applies Muysken's (2000) theory to classify types of code-mixing, Grice's (1975) theory to analyze types of conversational implicature, and Hoffmann's (1991) theory to identify the functions of code-mixing. This research employs a qualitative case study method, with data drawn from two podcast videos totaling approximately one hour and forty-nine minutes, uploaded to the YouTube channels of Azka Corbuzier and Deddy Corbuzier, from which 19 code-mixed utterances conveying conversational implicature were identified as the final data. The findings show that the types of code-mixing found are insertion, alternation, and a combination of insertion and alternation, while congruent lexicalization was not found. All data were classified as particularized conversational implicature. The dominant function of code-mixing in conveying conversational implicature is being emphatic. These findings suggest that code-mixing helps Azka Corbuzier convey conversational implicature in his conversations with Deddy Corbuzier on the YouTube podcast.